1981
DOI: 10.1007/bf01851007
|View full text |Cite
|
Sign up to set email alerts
|

Die allogene Lebertransplantation

Abstract: Although pig liver allograft induces a regular cellular immune response the transplanted live shows only mild injection or can be accepted. Long term survivors show a reduced cellular immunity in vitro involving the lack of donor-specific memory cells and the development of blocking antibodies. These immunoglobins are mainly considered to mediate the increased survival time of the grafted liver. They show anti-Ia-like specificities and their induction is favoured by the particular Ia- and SD-antigen pattern of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Bom van Noordloos et al [18], Vaiman et al [19], Flye et al [20], and Bockhorn [21] have shown a dependence on the strain combina tion and SLA compatibility, which has been confirmed in the rat by Zimmerman et al [22] and Tsuchimoto et al [23], However, our own previous experience [7], and the present data accord with that of Caine et al [24], and shows that up to 60% unimmunosuppressed pigs survive despite highly stimu latory MLC responses between donor and recipient pre-operatively. This is also borne out by the fact that the occurrence of rejec tion in human liver allografts appears unre lated to the lymphocyte crossmatch or to MHC mismatch [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Bom van Noordloos et al [18], Vaiman et al [19], Flye et al [20], and Bockhorn [21] have shown a dependence on the strain combina tion and SLA compatibility, which has been confirmed in the rat by Zimmerman et al [22] and Tsuchimoto et al [23], However, our own previous experience [7], and the present data accord with that of Caine et al [24], and shows that up to 60% unimmunosuppressed pigs survive despite highly stimu latory MLC responses between donor and recipient pre-operatively. This is also borne out by the fact that the occurrence of rejec tion in human liver allografts appears unre lated to the lymphocyte crossmatch or to MHC mismatch [25,26].…”
Section: Discussionmentioning
confidence: 99%